THE EFFECT OF PROGESTERONE INTRAVAGINAL DEVICE AND GONADOTROPIN RELEASING HORMONE ON FERTILITY IN POSTPARTUM DAIRY COWS - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
ABSTRACT The study was carried out to determine the effect of progesterone intravaginal devices and gonadotropin releasing hormone on fertility in postpartum dairy cows. Thirty two postpartum dairy cows having body condition score 3 4 were used in this study. The cows were devided randomly into 4 groups. Group I (CIDR 9 d), lI (CIDR 9 d + GnRH), DI (CIDR 15 (1), and IV (CIDR 15 d + GnRH). The GnRH was given at the time of insemination. The result of this study showed that the retention of CIDR devices and estrous induction was 100%. Estrous induction recorded on groups I, 11, BI and IV were 49.50 ± 1.51